Confucian ethics in the light of the Wu Xing text - Sun, Qingjuan (2017)
This thesis concentrates on the moral cultivation aspect of the Guodian Wu Xing manuscript and its theoretical connections with the Mengzi. First, the present thesis analyzes first the moral cultivation process in the Wu Xing text and argues that the process is completed through three progressive efforts: internalization, externalization, and harmonization. The effort of internalization is realized through the inner-heart approach and the outer-heart approach, respectively. By doing this, ren, yi, li, and zhi as external norms are turned into individual virtues. Sheng is different from the other four in the sense that it does not have any external forms but can only exist as an internal virtue. The effort of externalization is to externalize all the five individual virtues, that is, to make ren, yi, li, zhi, and sheng take form from within. This process is done through practice and results in de zhi xing (conducts of virtue 德之行). The last effort, harmonization, is to harmonize all the conducts of virtue. It relies on a qualitative change caused by quantitative accumulation of timely practice. Once this qualitative change occurs, all the five conducts of virtue will be in harmony. This harmony represents the achievement of de in a person. Moreover, moral achievements attained from each effort can be observed externally from one’s appearance. Second, this thesis also gives a reinterpretation of the Mengzi 6A: 4 on the nei (internality 內) and wai (externality 外) properties of virtue. It maintains that Gaozi and Mengzi are using different standards to distinguish the internal from the external in their debate. In particular, Gaozi adopts the family-boundary and states unequivocally that ren is internal and yi is external, whereas Mengzi utilizes the heart-boundary and his proposition is unclear. To figure out Mengzi’s standpoint, this thesis reconstructs the whole picture of his virtue system using metaphors in the Mengzi and concludes that virtues in the Mengzi are composed of different parts (root 根, sprout 端, and fruit實) and courses (bu yan er yu 不言而喻 and kuo er chong zhi 擴而充之), which constitute dynamic processes that embrace both internal and external dimensions as well as a remarkable transition stage from the internal towards the external dimension. Therefore, Mengzi actually holds that virtues integrate both internal and external dimensions. This view of Mengzi is a selective adoption and development of the Wu Xing’s notion of “de zhi xing.” Finally, this thesis presents a comprehensive analysis on issues concerning sheng and zhi. It proposes that sheng is a functional property in the Wu Xing. In addition to its extraordinary functions of hearing and knowing the way of the noble man, sheng also serves to regulate the other four individual virtues internally and their conducts of virtue externally. It is the regulative function of sheng that makes harmony possible in the Wu Xing. A comparative study is conducted on the discrepancies in the understanding of sheng and sheng ren between the Wu Xing and the Mengzi, which also reveals additional theoretical connections between the two literatures. This thesis holds that the Wu Xing precedes Mengzi to have signs of both the four-sprout theory and the kuo er chong zhi notion. Besides, it proposes that the cultivation process in the Wu Xing begins logically with zhi as an individual virtue and ends with the regulative function of sheng, and that the psychological state of you (apprehension 憂) plays a role as a prelude in the whole process. Taken together, this thesis sheds light on a deeper understanding of the moral cultivation notion in the Guodian Wu Xing text and reveals a closer theoretical connection between the Guodian Wu Xing and the Mengzi.